Zinc-α2-Glycoprotein Modulates AKT-Dependent Insulin Signaling in Human Adipocytes by Activation of the PP2A Phosphatase - Ceperuelo-Mallafré, Victòria; Ejarque, Miriam; Duran, Xavier; Pachón, Gisela; Vázquez-Carballo, Ana; Roche, Kelly; Núñez-Roa, Catalina; Garrido-Sánchez, Lourdes; Tinahones, Francisco J.; Vendrell, Joan; Fernández-Veledo, Sonia (PloS one, 2015)
Evidence from mouse models suggests that zinc-α2-glycoprotein (ZAG) is a novel anti-obesity adipokine. In humans, however, data are controversial and its physiological role in adipose tissue (AT) remains unknown. Here we explored the molecular mechanisms by which ZAG regulates carbohydrate metabolism in human adipocytes. ZAG action on glucose uptake and insulin action was analyzed. β1 and β2-adrenoreceptor (AR) antagonists and siRNA targeting PP2A phosphatase were used to examine the mechanisms by which ZAG modulates insulin sensitivity. Plasma levels of ZAG were measured in a lean patient cohort stratified for HOMA-IR. ZAG treatment increased basal glucose uptake, correlating with an increase in GLUT expression, but induced insulin resistance in adipocytes. Pretreatment of adipocytes with propranolol and a specific β1-AR antagonist demonstrated that ZAG effects on basal glucose uptake and GLUT4 expression are mediated via β1-AR, whereas inhibition of insulin action is dependent on β2-AR activation. ZAG treatment correlated with an increase in PP2A activity. Silencing of the PP2A catalytic subunit abrogated the negative effect of ZAG on insulin-stimulated AKT phosphorylation and glucose uptake but not on GLUT4 expression and basal glucose uptake. ZAG circulating levels were unchanged in a lean patient cohort stratified for HOMA-IR. Neither glucose nor insulin was associated with plasma ZAG. ZAG inhibits insulin-induced glucose uptake in human adipocytes by impairing insulin signaling at the level of AKT in a β2-AR- and PP2A-dependent manner.